2022
DOI: 10.1590/1678-992x-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Spodoptera frugiperda (Noctuidae) fed on transgenic maize can transfer Bt proteins to Podisus nigrispinus (Pentatomidae)

Abstract: An important concern with the use of genetically modified (GM) plants expressing Bacillus thuringiensis (Bt) insecticidal toxins is the deleterious effect on non-target organisms.The predatory stink bug Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae) is used in biological control programs and may be exposed to Bt toxins. This study evaluated the indirect effects of different Cry proteins on P. nigrispinus with the prey Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae), fed on simple or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Histological sections of the P. nigrispinus midgut shows the effects of proteins Cry1F, Cry1A.105, and Cry2Ab2, with histopathological changes, after predating Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) fed on GM Bt-maize but not being lethal to 3 rd trophic level (Souza et al, 2021). In additional, other studies showed that the Cry1Ac toxin caused ultrastructural changes in the digestive cells of the predatory stink bug P. nigrispinus when it fed on S. frugiperda that had consumed GM Bt-cotton expressing the toxin (da Cunha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Histological sections of the P. nigrispinus midgut shows the effects of proteins Cry1F, Cry1A.105, and Cry2Ab2, with histopathological changes, after predating Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae) fed on GM Bt-maize but not being lethal to 3 rd trophic level (Souza et al, 2021). In additional, other studies showed that the Cry1Ac toxin caused ultrastructural changes in the digestive cells of the predatory stink bug P. nigrispinus when it fed on S. frugiperda that had consumed GM Bt-cotton expressing the toxin (da Cunha et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, biomass feedstocks of all generations also have functional uses such as biomass power generation, heat supply, and hydrogen production in addition to preparing liquid fuels [186]. What's more, biomass can be used not only for energy but also for compost [187], feed [188], biochar [132]. It can also be processed into renewable tableware [189], not necessarily as a fuel or energy source.…”
Section: Feedstock Supplymentioning
confidence: 99%
“…La estimación del parámetro de producción de adultos consistió en una cámara de desarrollo de inmaduros (larvas) y producción de adultos, donde se evaluaron tres tratamientos correspondientes a 3.500, 4.500 y 5.500 huevos viables de T. solanivora por cámara de desarrollo. La producción de adultos se determinó desde el comienzo de la emergencia de los insectos con el registro diario y hasta comprobar que las pupas presentes aún eran viables mediante movimiento y turgencia (Souza et al 2021).…”
Section: Producción De Huevos Y Adultos De Tecia Solanivora En Labora...unclassified